How Human Subsistence Strategy Affected Fruit-Tree Utilization During the Late Neolithic and Bronze Age: Investigations in the Northeastern Tibetan Plateau - Liu, Fengwen; Zhang, Hucai; Li, Hu; Zhang, Xiaonan; Liu, Qi; Zhang, Yang; Li, Haoyu; Ma, Minmin (Frontiers in Plant Science, 2022)
Abstract: The history of fruit-tree utilization by prehistoric people has become an important issue that has attracted increasing attention in recent years. However, the question of how people used fruit trees has not yet been answered; in particular, the impacts of different subsistence strategies on human behavior regarding fruit-tree utilization (wild gathering or conscious cultivation) have not yet been considered. Here, we present the results of charcoal identification of fruit trees from 16 dated archaeological sites in the northeastern Tibetan Plateau (NETP) spanning the period c. 5200–2600 BP. We combine this with reported multidisciplinary evidence to explore the history of fruit-tree utilization as well as its relation to the subsistence strategy in the NETP during the late Neolithic and Bronze Age. Our results demonstrate that Rosaceae (Prunus L., Padus Mill., Maloideae, and Malus Mill.), Elaeagnaceae (Hippophae L. and Elaeagnus angustifolia L.), and Rhamnaceae (only Ziziphus Mill.) were used by people in the NETP, and there was a downward trend in the use of fruit trees during the late Neolithic and Bronze Age. This is in notable contrast to the situation in the Chinese Loess Plateau in the parallel period. The fruit trees used by people in the NETP were likely gathered from the wild rather than consciously cultivated, and the subsistence strategy of agropastoralism may have played a significant role during the processes.